Ultra rapid direct heating synthesis of ZnO nanorods with improved light trapping from stacked photoanodes for high efficiency photocatalytic water splitting. (1st August 2017) - Lee, Wei Cheat; Fang, Yuanxing; Commandeur, Daniel; Qian, Rong; Al-Abdullah, Zainab T Y; Chen, Qiao
Abstract: An ultra rapid growth method for vertically aligned ZnO nanorod (NR) thin films on metal meshes was developed using a direct heating synthesis technique. A typical NR growth rate of 10 μ m h −1 was achieved. The effects of the applied heating power and growth duration on the morphologies of ZnO nanostructures were examined. High density surface defects were formed on the ZnO NRs, which is responsible for slow charge recombination and high efficiency in the photoelectrochemical (PEC) water splitting process. The light absorption for a photoanode was significantly improved by light trapping using a 3D stacked metal mesh photoanode structure. With the internal reflection between the stacked photoanodes, the final light leakage is minimised. The light absorption in the stacked photoanode is improved without restricting the charge transportation. In comparison with a single mesh photoanode and a chemical bath deposition grown flat photoanode, the PEC water splitting efficiency from the stacked photoanode was increased by a factor of 2.6 and 6.1 respectively.